Development of Blockchain Based System for Secure Student Data Management - Ariesya Aprillia; Ana Theriana; Syaifuddin Syaifuddin; Fhia Amelia; Ramiro Santiago Ikhsan (IAIC Bangun Bangsa, 2026)
Student data management in Indonesian higher education institutions continues to face challenges such as data duplication, academic record manipulation, limited transparency, and weak interoperability caused by centralized databases. These issues hinder institutional credibility, administrative efficiency, and trusted academic governance. This study aims to conceptually develop a blockchain based framework to enhance data integrity, transparency, and efficiency in student data management. Using a qualitative descriptive and comparative approach, the research analyzes existing blockchain models and integrates technological and managerial perspectives to design a permissioned blockchain system supported by smart contracts. The proposed framework focuses on automating academic data validation, strengthening access control, and enabling secure inter-institutional data exchange. Comparative findings indicate that blockchain offers immutability, traceability, and accountability, positioning it as a transformative innovation for academic governance. The study provides a conceptual foundation for universities and policymakers to adopt secure and interoperable blockchain-based academic data systems aligned with Indonesia digital transformation agenda in higher education. Future research is recommended to simulate or pilot the model for practical evaluation and implementation.